Financial Performance Management Of Cooperative High School 1 Merapi East School Based On Solvency Ratio - Brace Donius; Ike Apriani (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
School cooperatives are meant to support school learning for instant kinds of activities. The meaning is achieving the level of economic needs among students and increasing a sense of responsibility, discipline, loyal friends, and the democratic spirit of students which is very useful for the development of the nation and the country. The financial report for Sundjaja and Barlian said that the report presented the results of the accounting process used as a means of communication by some parties. This person is the person who manages and has an interest in financial information or industrial activities. Financial Statement Analysis is the tools and methods used in carrying out financial report analysis that have a universal purpose and relate to data and are closely related to making estimates as well as conclusions as well as benefits in the analysis. business. Financial Statement Analysis which is also used in this research includes the ratio analysis procedure, namely the Solvency Ratio. This researcher uses a quantitative research method, which is a research method based on the philosophy of positivism, the sampling technique is tried randomly, not only that use research instruments as a means of collecting information, otherwise the analysis of data is statistically quantitative to test established hypotheses. The illustration from this research is the East Merapi 1 Public High School cooperative. The final result obtained from this research is that the school cooperative at SMA Negeri 1 Merapi Timur is liquid because there are no loans to other parties from outside and there is no establishment of business units for buying and selling school equipment but only engaged in the savings and loan business unit, still quite solvable because it is only engaged in one area of work, namely savings and loans, it has not yet made a profit because there are still a lot of funds that are still in the hands of its members and its activities are quite good because these funds continue to flow from other members to other members.